RISKS, COPING AND ROLES OF ACCESS TO FINANCIAL SERVICES - MEHERUN AHMED; BAQUI KHALILY (Annals of the University of Petrosani: Economics)
Households move strategically to smooth consumption in the event of economic shocks. This paper comprehensively analyzes various coping schemes adopted by households in the event of different types and intensity of economic shocks. We conclusively find that erosive coping is a dominant strategy for households except asset shocks. It is also evident that the higher the total loss suffered the greater is the likelihood of adopting erosive coping schemes for any of the three economic shocks. Contrary to the findings related to asset shocks, the household is high likely to adopt erosive savings, help from relatives in case of economic shocks. In addition to these two methods, households also takes up new loans and mortgaging land when it encounters expenditure shocks. The househols is more prone to adopt multiple strategies in case of income and expenditure shocks.